Domestics dogs as a reservoir of Leptospira spp and Toxoplasma gondii in a peasant community of the cloud forest of northeastern Peru - Carlos Erazo, Nancy (2023)
The aim of this study was to identify the role of domestic dogs as reservoirs of Leptospira spp and Toxoplasma gondii in the Rural Community of Corosha, department of Amazonas, Peru, through the analysis of prevalence and epidemiological characteristics, as well as tenure associated with dog positivity. A survey was carried out on the dog owners and blood samples were taken. In total, 55 samples were analyzed by the Microscopic Agglutination Test (MAT) for the identification of anti-Leptospira spp antibodies and 62 samples with the Indirect Hemagglutination technique (HAI) for anti-T. gondii. The seroprevalence of Leptospira spp was 82.3%, detecting antibodies against the Grippotyphosa (58.2%), Icterohaemorrhagiae (54.6%), Pomona (40.0%), Canicola (32.7%), Bratislava (30.9%) and Georgia (21.8%) serovars. Dogs with access to the river showed a higher prevalence of Leptospira (94.9%) compared to individuals without access (68.8%) (p<0.05). Likewise, 37.1% of the evaluated dogs were seropositive for T. gondii. The study reveals the circulation of Leptospira spp and T. gondii in domestic dogs of the rural community of Corosha.